MODEL OF COMMUNICATION OF THE PRINCIPAL IN INCREASING THE QUALITY OF EDUCATION AT MADRASAH - A’yun, Qurrotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the communication model used by the principal in improving the quality of education at MA Nurul Jadid. The research uses a descriptive qualitative approach. The results of the study show that there are 3 communication patterns carried out by the principal of MA Nurul Jadid, namely interpersonal communication, group communication, and mass communication. The communication carried out by the principal of MA Nurul Jadid in improving the quality of education is a form of communication in interacting with teachers, students, and parents. The media used are discussion (consultation), giving actions or examples, telephone, website, and whatsapp. Therefore, with the communication patterns that have been implemented properly, it can create effective communication